Efficacy of the Levonorgestrel-Releasing Intrauterine System on IVF-ET Outcomes in PCOS With Simple Endometrial Hyperplasia. (June 2015) - Bian, Jiang; Shao, Hongfang; Liu, Hua; Li, Hui; Fang, Lu; Xing, Changying; Wang, Lihong; Tao, Minfang
Objective: This study investigated the in vitro fertilization (IVF) outcome of levonorgestrel-releasing intrauterine system (LNG-IUS) pretreatment for simple endometrial hyperplasia (EH) in patients with polycystic ovary syndrome (PCOS) undergoing IVF embryo transfer (IVF-ET). Methods: One hundred ninety patients with PCOS and simple EH without cytologic atypia were allocated randomly to 2 independent arms, that is, the LNG-IUS group (90 patients) and the non-LNG-IUS group (100 patients). Four hundred fourteen patients with PCOS without endometrial disease comprised the control group. Each patient was reevaluated by transvaginal ultrasonography (TVS) and endometrial biopsy after 6 months. For each patient, IVF outcome measures, such as number of recombinant follicle-stimulating hormone, endometrial thickness on human chorionic gonadotropin (HCG) day, hormone levels (progesterone, luetinizing hormone, and serum estradiol) on HCG day, number of oocytes, fertilization rate, clinical pregnancy rate, and miscarriage rate were compared among the 3 groups. Results: In general, the 3 groups did not differ with respect to the main clinical and biochemical data. After 6 months, patients in LNG-IUS group had an EH resolution rate of 87.77%. In the non-LNG-IUS group, the resolution rate was 15.00%, and 3% of these patients showed progression of EH. The clinical pregnancy rates in the non-LNG-IUS group were significantly lower (28.04%) than that in the LNG-IUS group (46.06%) and the control group (44.65%). The miscarriage rate was highest in the non-LNG-IUS group, but no significant difference in miscarriage rate existed among the 3 groups. Conclusion: The study illustrates that the LNG-IUS can be safely used for 6 months as a treatment for patients with PCOS and simple EH. Additionally, use of the LNG-IUS can increase the clinical pregnancy rates and implantation rates of patients with PCOS and simple EH who undergo gonadotropin-releasing hormone agonist IVF-ET protocols.